Contribution of Short Chain Fatty Acids to the Growth of Pseudomonas aeruginosa in Rhinosinusitis - Cho, Do-Yeon; Skinner, Daniel; Hunter, Ryan C.; Weeks, Christopher; Lim, Dong Jin; Thompson, Harrison; Walz, Christopher R.; Zhang, Shaoyan; Grayson, Jessica W.; Swords, William E.; Rowe, Steven M.; Woodworth, Bradford A. (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Chronic rhinosinusitis (CRS) is characterized by complex bacterial infections with persistent inflammation. Based on our rabbit model of sinusitis, blockage of sinus ostia generated a shift in microbiota to a predominance of mucin degrading microbes (MDM) with acute inflammation at 2 weeks. This was followed by conversion to chronic sinus inflammation at 3 months with a robust increase in pathogenic bacteria (e.g. Pseudomonas). MDMs are known to produce acid metabolites (short chain fatty acids (SCFA)) that have the potential to stimulate pathogen growth by offering a carbon source to non-fermenting sinus pathogens (e.g. Pseudomonas). The objective of this study is to evaluate the concentrations of SCFA within the mucus and its contribution to the growth of Pseudomonas aeruginosa. Methods: Healthy and sinusitis mucus from the rabbit model were collected and co-cultured with the PAO1 strain of P. aeruginosa for 72 hours and colony forming units (CFUs) were determined with the targeted quantification of three SCFAs (acetate, propionate, butyrate). Quantification of SCFAs in healthy and sinusitis mucus from patients (with and without Pseudomonas infection) was also performed via high performance liquid chromatography. Results: To provide evidence of fermentative activity, SCFAs were quantified within the mucus samples from rabbits with and without sinusitis. Acetate concentrations were significantly greater in sinusitis mucus compared to controls (4.13+/-0.53 vs 1.94+/-0.44 mM, p<0.01). After 72 hours of co-culturing mucus samples with PAO1 in the presence of mucin medium, the blue-green pigment characteristic of Pseudomonas was observed throughout tubes containing sinusitis mucus. CFUs were significantly higher in tubes containing mucus samples from sinusitis (8.4x10^9+/-4.8x10^7) compared to control (1.4x10^9+/-2.0x10^7) or no mucus (1.5x10^9+/-2.1x10^7) (p<0.0001). To provide evidence of fermentative activity in human CRS with P. aeruginosa, the presence of SCFAs in human mucus was analyzed and all SCFAs were significantly higher in CRS with P. aeruginosa compared to controls (p<0.05). Conclusion: Given that SCFAs are exclusively derived from bacterial fermentation, our evidence suggests a critical role for mucin-degrading bacteria in generating carbon-source nutrients for pathogens. MDM may contribute to the development of recalcitrant CRS by degrading mucins, thus providing nutrients for potential pathogens like P. aeruginosa.